2020
DOI: 10.1302/2046-3758.96.bjr-2019-0258.r1
|View full text |Cite
|
Sign up to set email alerts
|

Limb position influences component orientation in Oxford mobile bearing unicompartmental knee arthroplasty

Abstract: Aims The mobile bearing Oxford unicompartmental knee arthroplasty (OUKA) is recommended to be performed with the leg in the hanging leg (HL) position, and the thigh placed in a stirrup. This comparative cadaveric study assesses implant positioning and intraoperative kinematics of OUKA implanted either in the HL position or in the supine leg (SL) position. Methods A total of 16 fresh-frozen knees in eight human cadavers, without macroscopic anatomical defects, were selected. The knees from each cadaver were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…A recent study determined that surgical cut errors in UKA-M were effected by limb posture. 43 They found similar errors to those used in this study, however they found significantly higher errors in the internal rotation of the medial component when the traditional supine leg position was used, rather than the manufacturer-recommended hanging leg position. The extreme of the internal rotation error associated with the supine position was greater than the error assessed in this study.…”
Section: Discussionsupporting
confidence: 70%
“…A recent study determined that surgical cut errors in UKA-M were effected by limb posture. 43 They found similar errors to those used in this study, however they found significantly higher errors in the internal rotation of the medial component when the traditional supine leg position was used, rather than the manufacturer-recommended hanging leg position. The extreme of the internal rotation error associated with the supine position was greater than the error assessed in this study.…”
Section: Discussionsupporting
confidence: 70%
“…The inclusion criteria were as follows: (1) After approved by the Ethics Committee of our institution (KY2020124) , a randomized controlled trial was conducted on the basis of pre-and postoperative outpatient clinical charts. From October 2017 to June 2018, 64 consecutive and unselected patients who underwent primary, medial UKA in our institution were involved in our study.…”
Section: Methodsmentioning
confidence: 99%
“…Unicompartmental knee arthroplasty (UKA) is a safe and effective intervention for end-stage knee arthritis con ned to the medial compartment [1] [2]. Compared with total knee arthroplasty (TKA), preservation of cruciate ligaments and less bone loss allowed UKA to attain a earlier recovery, less perioperative complications, and a better range of motion(ROM) of knee [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of cadaveric research is that it is more intuitive; however, it is not helpful for in-depth research. [1][2][3] First, it is difficult and expensive to obtain cadaveric specimens. Second, large joints are challenging to preserve, significantly limiting intact joint research.…”
Section: Introductionmentioning
confidence: 99%
“…To better understand the knee joint's function and disease mechanism, many biomechanical studies have been carried out based on cadaveric specimens. The advantage of cadaveric research is that it is more intuitive; however, it is not helpful for in‐depth research 1–3 . First, it is difficult and expensive to obtain cadaveric specimens.…”
Section: Introductionmentioning
confidence: 99%